Law of copyright: comparative perspectives - "Chawla, Alka" (Gurgaon, 2013)
The judiciary is witnessing a significant increase in disputes relating to copyright law which substantiates the fact that copyright owners are becoming aware of their legal rights.
Keywords: Copyright law